Evaluation of different ways to identify persistent positivity of lupus anticoagulant in systemic lupus erythematosus - Laurence S Magder; Mertcan Avci (Lupus Science and Medicine)
Objective Persistent positivity for lupus anticoagulant has been associated with an increased risk of thrombosis among patients with SLE. Persistent positivity is often defined as having two positive assessments separated by more than 90 days. Our objective was to determine whether frequent repeated lupus anticoagulant testing would identify more patients with persistent positivity, and whether the additional patients identified were still at increased risk of thrombosis.Methods Using a large longitudinal cohort with frequent lupus anticoagulant testing, we compared three different hypothetical clinical strategies for identifying persistent positivity: (1) assessment of lupus anticoagulant twice more than 90 days apart; (2) assessment of lupus anticoagulant annually, with repeat testing if an annual assessment was positive; and (3) assessment of lupus anticoagulant 16 times (approximately quarterly for 4 years). The prevalence of persistent positivity was compared between the approaches and by demographic subgroups. Subgroups based on these definitions were compared with respect to the risk of thrombosis in subsequent follow-up using discrete survival analysis.Results Among the 785 patients included in our analysis, the prevalence of persistent lupus anticoagulant as defined by the first two patient assessments was 4.3%. Annual assessment resulted in a prevalence of 6.6%, and using all 16 assessments resulted in a prevalence of 10.5%. The prevalence was substantially higher in men than in women, and in Caucasians than in African-Americans (p<0.01 for all comparisons). The rate of thrombosis was significantly elevated among those with persistently positive lupus anticoagulant by any definition (HR ranging from 2.75 to 3.42) relative to those without persistently positive lupus anticoagulant.Conclusion While there are other risk factors for thrombosis (including other antiphospholipid subtypes), more frequent testing (not limited to twice over 3 months) for lupus anticoagulant would be useful for identifying more patients with SLE at elevated risk for thrombosis.